Eclecticism and Principles in Digital Painting - Adil Zrar Ameen; Falah Hassan Shakrchi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Digital painting is all the work done by technology. It is primarily used to produce creative works of art, such as paintings, cartoon characters, landscapes, expressive paintings, and so on. The importance of digital technology in arts and humanities studies is growing. Digital art is not a subset of other arts in that it employs digital technology as an essential part of the creative or display process. The purpose of this study is to demonstrate how the selection works as well as the fundamentals of digital painting. The researcher dealt with eclecticism in contemporary art, reviewing the most important characteristics of that era of art. As for the principles of digital painting, the researcher referred to qualities such as: contrast, balance, expression, rhythm. In the third chapter of this study, the researcher used the descriptive analysis method to present the principles and how to implement artworks and run the computer drawing program, multimedia device, smart phone applications and devices. The theoretical framework deals with the topic of the current research by observing the concept of eclecticism in modern art. In this topic, the researcher analyzed the eclecticism of modern art through the features and characteristics of modern art. The researcher referred to characteristics such as: contrast, balance, expression, rhythm. In this study, the researcher used descriptive analysis to present the principles and how to implement and operate a computer drawing program, a multimedia device, smartphone apps and iPads to express digital art painting. The mentioned methodological approaches were the result of the researcher's empirical studies of graphical composition for several digital applications. So digital drawing is a modern instrument in the art of painting in which academics can develop their work using modern technology such as software programs, smartphone apps, and apps to generate amazing and three-dimensional digital images.